Open Textbook Proof-of-Concept via Connexions - Baker, Judy; Thierstein, Joel; Fletcher, Kathi; Kaur, Manpreet; Emmons, Jonathan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
To address the high cost of textbooks, Rice University’s Connexions and the Community College Open Textbook Project (CCOTP) collaborated to develop a proof-of-concept free and open textbook. The proof-of-concept served to document a workflow process that would support adoption of open textbooks. Open textbooks provide faculty and students with a low cost alternative to traditional publishers’ textbooks and can help to make higher education more affordable. Connexions provides a publishing platform for open textbook projects. The CCOTP acted as a liaison between community college faculty, open textbook authors, and Connexions. Challenges to the production and adoption of open textbooks include 1) faculty members’ and students’ expectations of high production quality and ancillaries for open textbooks, 2) methods for documenting and maintaining control over various versions, and 3) the process of converting existing open content to digital and accessible formats. Connexions holds promise as a means to overcome these challenges. Connexions identified lessons learned about open textbook production, such as the importance of a style guide, the advantage of assembly-line workflow, and the importance of naming conventions and standard math authoring tools, Connexions also identified lessons learned about open textbook use by students and faculty, e.g., the value of availability and customizability, the importance of interactivity, the difference in how faculty and students view modularity, and the importance of textbook reading navigational aids. The authors note that the CCOTP recommends using Connexions as the common repository for open textbook content in an effort to provide greater national and international access.